EFEKTIVITAS APLIKASI i-KURMA DALAM PROSES PEMUTUSANPEMBERIAN PEMBIAYAAN DI PT BANK SYARIAH INDONESIA KC LANGSA DARUSSALAM - Nofiantoro, Wahyu; Febriani, Ulfa (Jurnal Vokasi Indonesia, 2021)
The process of terminating the provision of financing in the Banking Financing Operation division at PT Bank Syariah Indonesia KC Langsa Darussalam uses the i-kurma application created by the central PT BSI. The implementation of the i-kurma application is primarily to save time in the process of disbursing financing to improve the performance of work units that carry out financing activities. The purpose of this study was to assess the effectiveness of the implementation of the i-Kurmad application at PT BSI KC Langsa Darussalam. This research is a quantitative research that uses a questionnaire as a data collection technique. This study analyzes the factors that influence the use of the i-Kurma application using a modified DeLone and McLean model. To test the interrelationships between variables will be tested using Structural Equation Model (SEM) using the SmartPLS 3 program. The results obtained state the factors that affect the effectiveness of the i-Kurma application in the process of deciding on financing, including Information Quality (IQ), System Quality ( SQ), Service Quality (SEQ), Use (U), User Satisfaction (US), and Net Benefit (NB). This is corroborated by the results of descriptive statistics which state that these factors have average results per variable which indicate user agreement that the i-kurma application effectively helps users' performance. The practical implication of this research is that the application of i-kurma helps in the process of deciding on the provision of financing. The quality of information is the main factor that has the most influence on the success of the i-kurma information system.